2007
DOI: 10.1111/j.1365-2958.2007.05620.x
|View full text |Cite
|
Sign up to set email alerts
|

The type III secretion system needle tip complex mediates host cell sensing and translocon insertion

Abstract: SummaryType III secretion systems (T3SSs) are essential virulence determinants of many Gram-negative bacterial pathogens. The Shigella T3SS consists of a cytoplasmic bulb, a transmembrane region and a hollow 'needle' protruding from the bacterial surface. Physical contact with host cells initiates secretion and leads to assembly of a pore, formed by IpaB and IpaC, in the host cell membrane, through which proteins that facilitate host cell invasion are translocated. As the needle is implicated in host cell sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
314
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(327 citation statements)
references
References 46 publications
11
314
1
1
Order By: Relevance
“…It has been also reported that Shigella IpaB, a homologue of Salmonella SipB, may be associated with the bacterial surface (Menard et al, 1994;Mills et al, 1988;Watarai et al, 1995;Veenendaal et al, 2007). Therefore, we first sought to confirm that SipB protein was present on the bacterial outer membrane.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…It has been also reported that Shigella IpaB, a homologue of Salmonella SipB, may be associated with the bacterial surface (Menard et al, 1994;Mills et al, 1988;Watarai et al, 1995;Veenendaal et al, 2007). Therefore, we first sought to confirm that SipB protein was present on the bacterial outer membrane.…”
Section: Resultsmentioning
confidence: 92%
“…It was recently reported that IpaB and IpaD, the translocon proteins of Shigella, can be localized on the bacterial cell surface (Olive et al, 2007;Veenendaal et al, 2007). However, the surface localization of PopB and PopD of Pseudomonas, BopB and BopD of Bordetella, and BipB and BipD of Burkholderia have not yet been characterized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations